2020
DOI: 10.3390/economies8020034
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency of Smallholder Agriculture in Developing Countries: The Case of Ethiopia

Abstract: The efficient use of inputs is indispensable in many developing countries, such as Ethiopia. This study assesses the level and determinants of technical efficiency of smallholder farmers using the true fixed effects (TFE) model. The TFE model separates inefficiency from unobserved heterogeneity. Empirical data come from four rounds of panel data (1994–2009) from the Ethiopian rural household survey (ERHS). A one-step maximum likelihood estimator was employed to estimate the Cobb-Douglas stochastic frontier pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 57 publications
11
41
1
Order By: Relevance
“…The same result is obtained by [11,41,42]. In line with the results of [43,44], land size was found to be the most important factor of production with the highest level of elasticity (1.658). This indicates that farmers are operating in an irrational zone of production (increasing return to land).…”
Section: Econometric Results Of the Sfpf Model Estimationsupporting
confidence: 84%
See 1 more Smart Citation
“…The same result is obtained by [11,41,42]. In line with the results of [43,44], land size was found to be the most important factor of production with the highest level of elasticity (1.658). This indicates that farmers are operating in an irrational zone of production (increasing return to land).…”
Section: Econometric Results Of the Sfpf Model Estimationsupporting
confidence: 84%
“…The average TE score in the study areas is 44.33% with variation (SD = 0.211), indicating that there is wider room for increasing crop production in the study areas through mitigating the technical (in)efficiency of smallholder farmers without additional investment in novel agricultural technologies. This finding is lower than the TE scores estimated by empirical researchers in African countries (59%, 66.18%, 74% and 78% for Ethiopia by Tenaye [43], Geffersa [46], Seyoum [47] and Abate [48], respectively; 78% in Papua New Guinea by Coelli and Fleming [21]; and 82% for Rwanda by Ngango and Kim [49]). Bogale and Bogale [50] also found that TE scores range from 77 to 97% for modern and traditional irrigation scheme user farmers in Ethiopia.…”
Section: Econometric Results Of the Technical (In) Efficiency Modelcontrasting
confidence: 56%
“…Therefore, it enables farmers in maximizing their output at efficient cost of production. This finding is consistent with the results reported by several authors in the literature, such as ( Kifle et.al (2017) and Tenaye (2020).…”
Section: Determinants Of Teff Inefficiencysupporting
confidence: 94%
“…Assessing determinants of agricultural production efficiencies is more important than merely presenting a set of efficiencies indices for designing agricultural policy to improve smallholders' agricultural productivity and efficiencies and hence reduce resource waste and improve farmers' livelihoods (Tenaye, 2020). Table 5 illustrates the socio-economic, demographic, farm characteristics and institutional factors that affect inefficiency in teff production.…”
Section: Determinants Of Teff Inefficiencymentioning
confidence: 99%
See 1 more Smart Citation